La fonction créative du stéréotype dans le récit bref en France au XVIe siècle - Pietrzak, Witold Konstanty (Romanica Silesiana, 2021)
In premodern literature, stereotype, called locus communis, had to play an important role inherited from Greek and Latin Antiquity’s rhetorics. In particular, it served as source of convincing arguments appropriate to discuss philosophical, theological or moral questions. The concept of common place has also found its use in short stories of 16th century. Firstly, in the realm of invention, when authors adapted narrative plots taken from written tradition; secondly, in the realm of elocution, when they employed topic images and sentences. The aim of this paper is to elucidate those two meanings of stereotype in French nouvelles published in that time.